Identification of BRCA1 As a Potential Biomarker for Insulin-Like Growth Factor-1 Receptor Targeted Therapy in Breast Cancer - Tali Cohen-Sinai; Tali Cohen-Sinai; Zoya Cohen; Haim Werner; Haim Werner; Raanan Berger (Frontiers in Endocrinology, 2017)
The insulin-like growth factor-1 receptor (IGF1R) emerged in recent years as a promising therapeutic target in oncology. Identification of potential biomarkers capable of predicting response to IGF1R-targeted therapy is of cardinal importance. Tumor suppressor BRCA1 has important roles in multiple pathways, including gene transcription, DNA damage repair, and control of apoptosis. Early studies have identified the IGF1R gene as a downstream target for inhibitory regulation by wild-type, but not mutant, BRCA1. The aim of the present study was to evaluate the hypothesis that the mutational status of BRCA1 may influence the ability of IGF1R-directed therapies to efficiently inhibit the IGF1R axis. Using breast cancer-derived cell lines expressing a wild-type or a mutant BRCA1, we demonstrate that the capacity of MK-0646, a monoclonal antibody antagonist to the human IGF1R, to inhibit insulin-like growth factor-1-stimulated IGF1R and downstream mediators’ phosphorylation was impaired in mutant BRCA1-expressing cell lines. In addition, the antibody was able to reduce proliferation of wild-type BRCA1-expressing cells but had a reduced inhibitory effect in mutant BRCA1-expressing cells. In summary, our data indicate that the mutational status of BRCA1 must be taken into account when selecting patients for IGF1R targeting protocols.